LEGAL EFFECTIVENESS IN THE PROBLEM OF APPLICATION FOR DISPENSATION OF MARRIAGE IN THE AMURANG STATE COURT (Case Study of Decision Number 5/Pdt.P/PN. Amr) - Basuki, Astin Ratri Nur Anggraini (Universitas Negeri Semarang, 2024)
Marriage dispensation is an attachment of the opposite sex in marriage carried out by the prospective bride with her type but is not old enough to marry in accordance with applicable regulations. This study analyzes the effectiveness of the law in the case of a marriage dispensation application at the Amurang District Court (Decision Number 5/Pdt.P/PN. Amr). The method in this study uses a normative legal study, in this case a study using legal rules or regulations as a building system related to a legal event. This study finds that it needs to be reaffirmed and there is a need for consideration and redesign related to the marriage dispensation so that there is no overlapping of regulations in its application and there is no legal loophole. This study concludes that, although various theories and regulations of the law are able to explain the problem of marriage dispensation, an in-depth analysis of these aspects is needed, so that a complete picture is obtained. This research needs counseling or socialization by the government to community members regarding the minimum age for marriage according to the latest regulations and influencing understanding related to the application of community marriage dispensation.